IMPROVING NETWORK-BASED CALENDAR SCHEDULING IN CONSTRUCTION WORK PLANNING (Eureka Journal of Civil, Architecture and Urban Studies, 2025)
In this article, the significance of network-based scheduling in the planning of contemporary construction works is examined, methods for improving such schedules are analyzed, and, based on the results obtained, recommendations are developed for their wide-scale practical application in accordance with construction norms and regulations, along with several specific proposals.
Keywords: Construction, planning, Gantt charts, linear schedules, network schedules, calendar plans, management, sequencing, model.